Motor control strategies and the effects of fatigue on golf putting performance - Grealy, M. A.; Ferguson Mathers, J. (Frontiers in Psychology, 2013)
This study investigated the strategies used by elite golfers to scale their putting actions to achieve putts of different distances. There were three aims; to determine if putting actions are scaled by manipulating swing amplitude as predicted by Craig et al. (2000), to establish the test-retest reliability of the Craig et al. model, and to evaluate whether elite golfers changed their putting scaling strategies when fatigued. Putting actions were recorded at baseline (time 1) and six months later (time 2) and after walking at 70% of maximum heart rate for one hour (time 3). Participants performed a total of 80 putts which varied in distance (1m, 2m, 3m, and 4m) at time 1 and time 2, and 100 putts to the same distances when they were fatigued (time 3). Multiple regression was used to examine how the golfers systematically changed the movement control variables in the Craig et al. model to achieve golf putts of different distances. Although swing amplitude was a strong predictor of putterhead velocity at ball impact for all of the participants at baseline (time 1), each golfer systematically changed aspects of the timing of their action. A comparison of the regression models between time 1 and time 2 showed no significant changes in the scaling strategies used, indicating that the Craig et al. model had good test-retest reliability. Fatigue was associated with a decrease in the number of putts that were successfully holed and significant changes in the scaling strategies used by three of the golfers, along with a trend for increasing the putterhead velocity at ball impact. These motor control changes in performance when fatigued were evident in successful putts indicating that even when these elite golfers were able to achieve the goal of holing the putt, moderate levels of fatigue were influencing the consistency of their performance. Theoretical implications for the Craig et al. model and practical implications for elite golfers are discussed.